Comparative evaluation of antiulcerogenic action of cryopreserved placenta extract under different modes of introduction - Chyzh, Mykola; Koshurba, Illia (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):310